The effects of Islamic spirituality paradigm in developing human capital programs for Islamic Financial institutions - Mhd. Sarif, Suhaimi; Ismail, Yusof (2013)
This paper explores the effects of Islamic spirituality paradigm in the mindset of Islamic financial institutions (ISFs) managers in developing human capital programs for ISFs. Islamic spirituality embraces a global perspective in terms of Oneness of God (Tawhidic) worldview that emphasizes on the sole submission, obedience and compliance to the Will of God. A competitive human capital programs with Tawhidic worldview provides a robust and comprehensive framework for managers in ISFs to work with and through competent and Tawhidic conscious employees to achieve organizational goals with efficiency and effectiveness. The integration of Islamic spirituality paradigm into the human capital programs enable businesses to create and sustain unique capacity to take advantage of the opportunities within the Islamic spirituality values. The study conducted personal interview with 10 student of Graduate School of Management International Islamic University Malaysia to explore the influence of Islamic spirituality paradigm in developing human capital programs for ISFs towards sustaining business competitiveness and strive for the betterment of Muslim Ummah. The results of the study show that the Islamic spirituality paradigm in the human capital programs is acceptable due to its emphasis on ISFs sustainability and betterment of humanity and Muslim Ummah, which by default includes all races of humanity. The operationalization of Tawhidic paradigm into human capital programs in the managerial skill and thinking should enable managers face global business challenges such as various regional trade alliances, different structures of global business organizations, and the global political/legal/economic environment. The theoretical implication for the study is on the integration of conventional managerial paradigm with Islamic spirituality. As for the practical implication for the study is the operationalization of Islamic spirituality into standard operating procedure. However, the results of the study are not conclusive and cannot be generalized. The study proposes future studies to use case studies method and to include key business stakeholders into the focus group discussion.